Evanescent field exposed microstructure fibers for optical sensing / Ng Wee Lit - Ng , Wee Lit (2018)
In this work, a modified photonic crystal fiber (PCF) that we refer to as Sunny PCF is proposed. The Sunny PCF with triangular interstitial air holes surrounding the core region increases the interaction of guided modes with the surrounding media. Full-vectorial finite element method (FEM) with perfectly matched layer boundary condition is used to design and simulate the evanescent field exposure and confinement loss characteristics of the proposed Sunny PCF. By adding sunny structure to a conventional PCF with air-filling ratio of 0.9, the highest achievable evanescent field exposure with negligible confinement loss can be significantly increased to 21.23% from 15.83% (for a comparative non-Sunny PCF) at the operating wavelength of 1550 nm. A preliminary Sunny PCF has been fabricated to prove the feasibility of the proposed structure. In the second part of this work, a new microstructured optical fiber (MOF) which can provide large cavities besides high evanescent field exposure and low confinement loss has been proposed, named Diamond Ring Fiber (DRF). Large cavities ease the infiltration of analyte and allow material coating for certain sensing applications. A silica core is supported by a thin ring in the middle of DRF, forming two large air holes in this fiber. Silica core surrounded by air allows high exposure of guided mode into the air with low confinement loss. 3 DRFs with different parameters have been fabricated using stack and draw method. An experiment has been carried out to study the beam profile of guided mode in different sizes of DRFs. Full-vectorial FEM with perfectly matched layer boundary condition is used to simulate the performance of the fibers using Scanning Electron Microscope (SEM) cross sectional images obtained. DRF with the core size of 0.8 μm can achieve high evanescent field exposure of 39.56% with low confinement loss of 0.027 dB/m at the wavelength of 1550 nm while providing two large cavities with the diameter of 4.2 μm and 10.8 μm respectively. This work is part of a larger effort in using surface plasmon resonance (SPR) for biosensing where the long term target is to adopt fiber technologies as a substrate as opposed to silicon based fabrication. A highly sensitive DRF based SPR sensor for refractive index sensing is then simulated. Chemically-active plasmonic material (gold) layer is coated inside the large cavity of DRF, and the analyte is infiltrated directly through the fiber. The light guiding properties and sensing performances are numerically investigated using FEM. The proposed sensor shows a maximum wavelength and amplitude interrogation sensitivity of 6,000 nm/RIU and 508 RIU-1, respectively over the refractive index range of 1.33-1.39. Additionally, it also shows a sensor resolution of 1.67×10-5 RIU and 1.97×10-5 RIU by following the wavelength and amplitude interrogation methods, respectively.